2019
DOI: 10.1029/2019jb017309
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Permeability Evolution During Repose Then Reactivation of Fractures and Faults

Abstract: Cyclic growth and decay of permeability in fractures is explored during repeated reactivation and repose of saw-cut fractures of Green River shale. These slide-hold-slide experiments are supported by measurements of fracture normal deformation and optical surface profilometry. Overall, we observe continuous permeability decay during repose (holds) and significant permeability enhancement during slow reactivation (slide). The permeability decay is accompanied by fault compaction. Both hydraulic aperture change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 45 publications
(79 reference statements)
6
30
0
Order By: Relevance
“…This is consistent with stresses on the in situ field scale fault-reactivation studies conducted by Guglielmi et al (2015), as well as with a series of experiments equally exploring processes in brittle failure and friction (e.g. Im et al 2018Im et al , 2019. We initiate each experiment by applying a confining stress of 3 MPa that is retained constant throughout the experiment.…”
Section: Experimental Setup and Proceduressupporting
confidence: 78%
See 2 more Smart Citations
“…This is consistent with stresses on the in situ field scale fault-reactivation studies conducted by Guglielmi et al (2015), as well as with a series of experiments equally exploring processes in brittle failure and friction (e.g. Im et al 2018Im et al , 2019. We initiate each experiment by applying a confining stress of 3 MPa that is retained constant throughout the experiment.…”
Section: Experimental Setup and Proceduressupporting
confidence: 78%
“…Previous studies have revealed complex interactions impacting permeability evolution during fracture reactivation; in that, shear slip deforms fracture walls through destruction and rearrangement of asperity contacts (Elsworth & Goodman 1986;Im et al 2019), which may result in permeability increases (e.g. Barton et al 1985;Wang et al 2017) or decreases (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically k min is set to zero in fitting experimental data, but keeping k min finite is useful for numerical purposes (the very low k min we use plays little role in the system behavior). Permeability also evolves due to a range of mechanical and chemical processes [35][36][37]39,48,49 . Here we introduce an idealization that captures two fundamental processes: permeability increase with slip and permeability reduction from healing and sealing processes over longer time scales.…”
Section: Resultsmentioning
confidence: 99%
“…Geologists document mineral-filled veins that provide evidence for episodic fluid pressurization events in which pore pressure locally exceeds the least principal compressive total stress 26,30,31 . The intermittency of fluid pressurization and release, a concept known as fault valving 30,31 , is a consequence of feedback between fault slip and deformation, which typically elevate permeability [32][33][34] , and healing and sealing processes, like pressure solution transfer, that reduce permeability [35][36][37][38][39] . These feedback effects are amplified by nonlinear dependence of permeability on effective normal stress due to mechanical compression of pores and microfractures 13,19,40 .…”
mentioning
confidence: 99%